Procedural technology of public relations in tourism: facilitation - Shayekina, Zh.M.; Mamrayeva, D.G.; Tashenova, L.V. (KSU publ., 2015)
In the article the practical aspects of using in the tourism business a procedural technology of public relations such as facilitation are discussed; the model and the basic steps of a process of facilitation were described; as one of the main tools of the facilitation process the «brainstorming» and it’s types and especially its application in practical activities of enterprises in the article are discussed in details; the classification of the facilitators, as well as those professional skills, which specialists of this profile should have were described.
Туризмдегі паблик рилейшенздің рəсімдік технологиялары: фасилитациялау
Процедурные технологии паблик рилейшенз в туризме: фасилитация
Keywords: public relations; facilitation; tourism industry; tourist enterprise; the recipient country; «brainstorming»; the facilitator